Efeito do tamanho, da alimentação na fase adulta e da idade no sucesso de cópula de machos de Ceratitis capitata (Diptera: Tephritidae) - Silva Neto, Alberto Moreira da (2012)
This work evaluated the influence of size on the copula success in Ceratitis capitata. To assure the production of different adult sizes (big and small), two groups of larvae had been fed with different protein concentrations. Subsequently, adult males of both groups had been compared in terms of copula success and amount of males who showed the first step of courtship (emission of sexual pheromone). The copula success in laboratory was evaluated with males in some ratios, which the number of big males with 5 days of life (an unique male) in relation to a gradual increase of small males with same age kept constant. The tested ratios had been 1:1, 1:2, 1:3, 1:4, 1:5, and 1:10. In the experiments of copula success in the 1:1 ratio and the ones of pheromone emission, they had been tested small male of different ages (5, 9 or 13 days), whereas the age of the big males kept constant (5 days). Experiments of copula success in the 1:1 ratio had been also carried through in field cage. It was proven that the big males had taken advantage in all the parameters analyzed in laboratory, emitting pheromone and having a bigger copula success, exactly when the age of the small males was varied. The size effect was so significant, that in the ratio of 1 big male for 10 small males,the females had still chosen the big males. In field cage, the results had been similar to the ones of laboratory.